Factors Influencing The Performance Of Health Workers Implementing Basic Emergency Obstetric Neonatal Care (PONED) At The Gowa District Health Center (International Journal of Environmental Sciences, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are important indicators in assessing the health status of a country. Although the trend of decreasing MMR and IMR in Indonesia shows improvement, these figures have not yet reached the SDGs target. Health centers with PONED services are at the forefront in handling obstetric and neonatal emergencies, so the performance of PONED implementers is very crucial. This study aims to analyze the influence of motivation, competence, organizational factors, work stress, work environment, and compensation on the performance of health workers implementing PONED in Gowa Regency. This study uses a quantitative approach with a cross-sectional design. The population in this study were all health workers at the PONED Health Center in Gowa Regency, with sampling using the proportionate stratified random sampling technique. Data were collected through questionnaires that had been tested for validity and reliability. Statistical tests used included the chi square test and logistic regression. The results of the analysis showed that all independent variables had a significant effect on the performance of PONED implementers (p <0.05). The Nagelkerke R Square value of 0.421 indicates that the independent variable has an influence of 42.1% on performance. The competency variable is the most dominant factor with a significance value of 0.014 and an Exp B value of 5.587. In conclusion, increasing motivation, competence, organizational management, work stress management, work environment conditions, and providing adequate compensation have an effect on improving the performance of PONED implementers. Competence is the main factor that needs to be strengthened to support the success of PONED services and reduce maternal and neonatal mortality rates.